Impact Of Shareholder Activism On Corporate Governance In China: Evidence From Companies Listed On The Shenzhen Stock Exchange “A” Shares - Shaokai Huang; Rui Xie (European Scientific Journal, ESJ, 2016)
This paper investigates impact of shareholder activism on corporate governance in China. The separation of ownership and management of companies often to some extent causes agency problems between shareholders and company managers. In Western countries, shareholders of a company usually actively participate in the company’s management and closely monitor management issues in order to enhance the company’s performance. At present, China’s securities market, along with institutional investors, is undergoing a rapid development. Nevertheless, problems in corporate governance among listed companies have been hindering the development of capital markets in China. Meanwhile, institutional investors have experienced significant growth. Moreover, national policies, as well as the split-share structure reform, further encourage the growth of institutional investors and their active participation in corporate governance for further promotion of the development of capital markets. Making empirical contribution, this paper tests how effective institutional investors participate in the governance of listed companies on the Shenzhen Stock Exchange (SZSE) “A” Shares after share reform in China. Results of empirical estimation indicate that China’s institutional investors do participate in corporate governance, but only to some extent. Positive behaviors of Chinese shareholders have played a favorable role in improving corporate governance.